Kinetics of the Thermal Decomposition of Mn(II) Complex of 8-Hydroxyquinoline-5-sulphonic Acid - Suresh Kumar, B.; Abhilasha, A.; Cyril, Wilma; Sobhana, D. (Asian Journal of Chemistry, 2010)
Mn(II) 8-hydroxyquinoline-5-sulphonic acid complex has been prepared, identified and thermally analyzed. The kinetics of the thermal decomposition of the complex has been studied using thermogravimetry (TG) in conjunction with DTG and differential scanning calorimetry (DSC). The kinetic parameters such as energy of activation, pre-exponential factor, entropy of activation and order parameter have been calculated for well defined and decomposition of stage. The equations used are Coats-Redfern and Madusoodanan-Krishnan-Ninan methods. The correlation co-efficient are found to be closer to unity. DSC has been used to calculate the enthalpy changes involved in the removal of water of crystallizations at all stages of decomposition. The negative value for the entropy of activation for all the three stages show that the complexes are more ordered in the activated state than in the reactants. The DTA studies on the complexes corroborate with the DTG curves.